Phagocytosis-inducing antibodies to Plasmodium falciparum upon immunization with a recombinant PfEMP1 NTS-DBL1α domain (2016)
Background: Individuals living in endemic areas gradually acquire natural immunity to clinical malaria, largely dependent on antibodies against parasite antigens. There are many studies indicating that the variant antigen PfEMP1 at the surface of the parasitized red blood cell (pRBC) is one of the major targets of the immune response. It is believed that antibodies against PfEMP1 confer protection by blocking sequestration (rosetting and cytoadherence), inducing antibody-dependent cellular-inhibitory effect and opsonizing pRBCs for phagocytosis. Methods: A recombinant NTS-DBL1α domain from a rosette-mediating PfEMP1 was expressed in Escherichia coli. The resulting protein was purified and used for immunization to generate polyclonal (goat) and monoclonal (mouse) antibodies. The antibodies’ ability to opsonize and induce phagocytosis in vitro was tested and contrasted with the presence of opsonizing antibodies naturally acquired during Plasmodium falciparum infection. Results: All antibodies recognized the recombinant antigen and the surface of live pRBCs, however, their capacity to opsonize the pRBCs for phagocytosis varied. The monoclonal antibodies isotyped as IgG2b did not induce phagocytosis, while those isotyped as IgG2a were in general very effective, inducing phagocytosis with similar levels as those naturally acquired during P. falciparum infection. These monoclonal antibodies displayed different patterns, some of them showing a concentration-dependent activity while others showed a prozone-like effect. The goat polyclonal antibodies were not able to induce phagocytosis. Conclusion: Immunization with an NTS-DBL1-α domain of PfEMP1 generates antibodies that not only have a biological role in rosette disruption but also effectively induce opsonization for phagocytosis of pRBCs with similar activity to naturally acquired antibodies from immune individuals living in a malaria endemic area. Some of the antibodies with high opsonizing activity were not able to disrupt rosettes, indicating that epitopes of the NTS-DBL1-α other than those involved in rosetting are exposed on the pRBC surface and are able to induce functional antibodies. The ability to induce phagocytosis largely depended on the antibody isotype and on the ability to recognize the surface of the pRBC regardless of the rosette-disrupting capacity.